Pengaruh Literasi Keuangan, Bunga Harian, dan Pencatatan Transaksi Digital Terhadap Pengelolaan Keuangan Pribadi Mahasiswa (Studi Kasus pada Pengguna SeaBank) - Lira Mareta Ramadhani; Aris Eddy Sarwono (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This research explores the impact of financial literacy, daily interest rates, and digital transaction tracking on university students’ personal financial management, specifically among SeaBank users. The study is motivated by the growing reliance on digital banking among students, which does not always translate to sound financial practices. Employing a quantitative method with a correlational design, the research involved 100 students from the Faculty of Economics and Business, Slamet Riyadi University Surakarta, selected through purposive sampling. Data were obtained via a structured questionnaire and analyzed using multiple linear regression. The findings reveal that each independent variable—financial literacy, daily interest, and digital transaction recording—exerts a significant and positive effect on students' personal financial management, both individually and collectively. These results emphasize the value of financial education and the effective use of digital banking features in fostering responsible financial behavior among students.